Complexity measures of geomagnetic indices in the last two solar cycles. (June 2021) - Alberti, T.; Consolini, G.; De Michelis, P.
Abstract: The SYM-H and AE geomagnetic indices can be considered as proxies of the response of the Earth's magnetosphere and ionosphere to solar magnetic activity. They indirectly monitor some electric current systems which flow in the ionosphere and magnetosphere whose dynamics are directly or indirectly related to the Sun–Earth interaction. Consequently, their temporal changes reflect processes occurring in the near-Earth space, which contribute differently to the overall magnetosphere–ionosphere dynamics. The aim of this work is to characterize the nature of these two geomagnetic indices by following a complex system approach and applying a novel formalism, e.g., the EMD-based dominant amplitude multifractal formalism (EMD-DAMF). A set of complexity measures, i.e., the Hurst exponent ( H ), the singularity width ( Δ α ) and the spectrum width ( Δ f ), is evaluated for both geomagnetic indices analyzing data recorded during the last two solar cycles. One of the most significant findings of this study is the absence of relevant differences between the two solar cycles in terms of complexity measures for both geomagnetic indices, suggesting that only the occurrence and the frequency of geomagnetic storms and substorms affect the Hurst exponent and the singularity widths of SYM-H and AE indices. Moreover, while the AE index complexity measures do not show a significant dependence on geomagnetic activity, the SYM-H index shows a reduction in its complexity features during the geomagnetic storms, manifesting a more persistent behavior and moving from a (mono)fractal-like to a multifractal-like behavior when passing from quiet to disturbed periods. Finally, our findings are consistent with previous works on the forecast horizon of the geomagnetic activity as well as on the relation between the high-latitude ionosphere and the low-latitude magnetosphere, thus confirming the importance of providing higher resolution measures for correctly dealing with several Space Weather phenomena. Highlights: A novel formalism is used to characterize complexity features of SYM-H and AE. Only the occurrence of geomagnetic storms and substorms affect complexity measures. The AE index has an intermittent character related to the magnetotail activity. The SYM-H index complexity measures change between quiet and disturbed periods. Complexity features are crucial for modeling purposes of the geomagnetic activity.